2020
DOI: 10.1109/tmi.2020.3014197
|View full text |Cite
|
Sign up to set email alerts
|

Tomographic Field Free Line Magnetic Particle Imaging With an Open-Sided Scanner Configuration

Abstract: Superparamagnetic iron oxide nanoparticles (SPIONs) have a high potential for use in clinical diagnostic and therapeutic applications. In vivo distribution of SPIONs can be imaged with the Magnetic Particle Imaging (MPI) method, which uses an inhomogeneous magnetic field with a field free region (FFR). The spatial distribution of the SPIONs are obtained by scanning the FFR inside the field of view (FOV) and sensing SPION related magnetic field disturbance. MPI magnets can be configured to generate a field free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 80 publications
0
41
0
Order By: Relevance
“…44,233 In terms of instrumentation, advancements in sensitivity have most frequently been from developments in coil design. 37,74,78,79,234,235 Regarding tracer development for enhanced sensitivity, the signal intensity is governed by the physical and inherent magnetic properties of the tracer, as with spatial resolution, but is mostly dependent on the Ms. 16,18,55 Although the detection sensitivity of MPI is strong currently, through significant advancement it has the potential to become comparable with that of exceptionally sensitive nuclear imaging techniques. 234 Given what has been discussed, the development of SPIONs with optimal sensitivity and spatial resolution performance has become a crucial part of MPI research.…”
Section: Effect Of Spions On Spatial Resolution and Sensitivity In Mpimentioning
confidence: 99%
See 2 more Smart Citations
“…44,233 In terms of instrumentation, advancements in sensitivity have most frequently been from developments in coil design. 37,74,78,79,234,235 Regarding tracer development for enhanced sensitivity, the signal intensity is governed by the physical and inherent magnetic properties of the tracer, as with spatial resolution, but is mostly dependent on the Ms. 16,18,55 Although the detection sensitivity of MPI is strong currently, through significant advancement it has the potential to become comparable with that of exceptionally sensitive nuclear imaging techniques. 234 Given what has been discussed, the development of SPIONs with optimal sensitivity and spatial resolution performance has become a crucial part of MPI research.…”
Section: Effect Of Spions On Spatial Resolution and Sensitivity In Mpimentioning
confidence: 99%
“…[378][379][380] Despite these obstacles, there has been sustained work on the translation and hardware scale-up. 42,43,79,235,381,382 In the design of a functional MPI brain imager, Mason et al developed simulation studies that demonstrated promising capabilities for human-scale systems. 383 In an alternative approach Graeser et al successfully presented a human-sized MPI hardware set-up, tailored for brain applications, that has low technical requirements for fast and flexible operation in a clinical environment.…”
Section: Clinical Translationmentioning
confidence: 99%
See 1 more Smart Citation
“…In this process, out-of-slice imaging artifacts must be addressed by either a 3D model-based reconstruction or further encoding along the bore. These approaches have been demonstrated in x-space 36 , 95 or system matrix 96 reconstructions. To assess the degree to which the detected nanoparticles near the surface of the specimen, it is important to have 3D knowledge of the surface location.…”
Section: Lumpectomy Specimen Imaging With Small-bore Scannermentioning
confidence: 99%
“…In 2019, Top analyzed the image quality of different FFL trajectories [ 18 ]. In 2020, Top presented the first open-sided MPI system, which can electronically scan the FOV with an FFL [ 24 ].…”
Section: Mpi Principlementioning
confidence: 99%